DAS Ampal Analisa Fungsi dan Pengaruh Bangunan Pengendali Banjir DAS Ampal Kota Balikpapan - Rossana Margaret Kadar Yanti; Edijatno Edijatno; Umboro Lasminto (SPECTA Journal of Technology, 2018)
Ampal Catchment Area has 25.273 km2 area and 4.699 km main river length, which planned to have 13 flood control construction. Until 2017, this catchment area has only three flood control construction. The watershed has only three built-in batters that are used to reduce the amount of flood discharge flowing on the Ampal river. Based on these conditions, it is necessary to analyze the magnitude of the difference of flood peak discharge on the existing condition (three bendali) compared with the condition of the plan (thirteen bendali). Therefore, analyzed the function and influence of flood control construction in Ampal Catchment Area by counting the flood peak discharge in each condition. From the analysis result, obtained the amount of peak discharge flowing in Ampal river existing condition is equal to 170,40 m3/s while at the condition of plan is equal to 83,80 m3/s. From the results of analysis, it is stated that the magnitude of the decrease of debit (ΔQ) after all the builds is 86.60 m3/s.